Bovine manure doses for agronomic and fiber characteristics of the BRS Rubi upland cotton = Doses de esterco bovino nas características agronômicas e de fibras do algodoeiro herbáceo BRS Rubi. - José Rodrigues Pereira (Agro@mbiente On-line, 2012)
In Paraíba, Brazil, a local market for family farming is the production of naturally colored cotton grown in agroecological regime. For solution of physicochemical and biological soil degradation of brazilian semiarid, where Caatinga biome predominates, one valuable agroecological practice is the organic adubation. Accordingly, it was aimed with the present work to study the influence of bovine manure doses (D0 - 0.0; D1 - 2.5; D2 - 5.0; D3 - 10.0; D4 - D5 and 20.0 - 40.0 Mg ha-1) on agronomic and fiber characteristics of the agroecological herbaceous cotton BRS Rubi crop in the arid region of that State, in the years 2008/2009 and 2009, and to define the best dose of this organic fertilizer for this system and this growing region. The treatments were arranged in a randomized block design, with four replications. It was performed combined analysisof variance of the experiments, being evaluated agronomic (stem diameter, plant height, yeild and boll weight) and fiber(percentage, length, strength, micronaire index, fiber short index, elongation and maturity of fibers) variables in the two yearsof cultivation. It was concluded that: there was influence of the bovine manure doses tested for the agronomic characteristicsbut not for the characteristics of the fibers of the herbaceous cotton colored BRS Rubi; the best dose was 18 Mg ha-1of bovinemanure (Maximum Economic Dose). = Na Paraíba, um nicho de mercado para a agricultura familiar é a produção de algodão naturalmente colorido ecultivado agroecologicamente. Para solução da degradação físico-química e biológica dos solos do semiárido brasileiro, onde o bioma caatinga predomina, uma prática agroecológica valiosa é a adubação orgânica. Nesse sentido, objetivou-se com o presente trabalho estudar a influência de doses de esterco bovino (D0 - 0; D1 - 2,5; D2 - 5; D3 - 10; D4 - 20 e D5 - 40 Mg ha-1) sobre características agronômicas e da fibra do algodoeiro herbáceo colorido BRS Rubi, sob cultivo agroecológico no Sertão Paraibano, durante dois anos agrícolas (2008/2009 e 2009), e definir a melhor dose deste fertilizante orgânico para este sistema e região de cultivo. Os tratamentos foram dispostos em um delineamento experimental de blocos casualizados, com quatro repetições. Foi realizada análise conjunta dos ensaios, sendo avaliadas variáveis agronômicas (diâmetro caulinar, altura daplanta, produtividade e peso dos capulhos) e das fibras (percentagem, comprimento, índice de fibras curtas, resistência, finura,alongamento e maturidade das fibras) nos dois anos de cultivo. Concluiu-se que houve influência das doses de esterco bovinotestadas sobre as características agronômicas, mas não sobre as características das fibras do algodão herbáceo colorido BRSRubi; a melhor dose foi de18 Mg ha-1 de esterco bovino (Dose Máxima Econômica).